RESILIENSI AKADEMIK MAHASISWA AKHIR: PERAN OPTIMISME DAN DUKUNGAN TEMAN SEBAYA - Danianta, Prames Berliana; Khotimah, Siti Khorriyatul (Psikosains: Jurnal Penelitian dan Pemikiran Psikologi, 2024)
Background: Resilience refers to the attitude of self-defense which is alwayscalm in completing all the processes that are undertaken. Objective: This studyaims to determine the relationship between optimism and peer support with theacademic resilience of final students. Method: The method used is correlationalquantitative with 385 subjects selected using random sampling technique. Datacollection was carried out using a Google form which was distributed via socialmedia using three variable scales. Result: The results of the data analysis showthat optimism is positively correlated with academic resilience. With details onthe optimism variable making an effective contribution of 21.8%, while the peersupport variable with academic resilience has a positive relationship with thevalue of the effective contribution to the peer support variable of 32.9%.Conclusion: So the F test produces a positive and significant relationship to thevariables of optimism and peer support with academic resilience, at 54.9% it isstated that these two variables have influence and 45.1% are influenced by othervariables.